2013
DOI: 10.1115/1.4024031
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pyromark 2500 Paint for High-Temperature Solar Receivers

Abstract: Pyromark 2500 is a silicone-based high-temperature paint that has been used on central receivers to increase solar absorptance. The radiative properties, aging, and selective absorber efficiency of Pyromark 2500 are presented in this paper for use as a baseline for comparison to high-temperature solar selective absorber coatings currently being developed. The solar absorptance ranged from ∼0.97 at near-normal incidence angles to ∼0.8 at glancing (80°) incidence angles, and the thermal emittance ranged from ∼0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(85 citation statements)
references
References 3 publications
2
83
0
Order By: Relevance
“…Previous studies [20,22] showed that the aging of the coating is mainly represented by the evolution of its solar absorptance. For this reason, the thermal emittance is assumed constant and the following simplified expression of the receiver efficiency is used (eq.…”
Section: Expression Of the Annualized Energymentioning
confidence: 99%
“…Previous studies [20,22] showed that the aging of the coating is mainly represented by the evolution of its solar absorptance. For this reason, the thermal emittance is assumed constant and the following simplified expression of the receiver efficiency is used (eq.…”
Section: Expression Of the Annualized Energymentioning
confidence: 99%
“…Excellent thermal stability is also crucial for ensuring solar absorbers to operate properly with efficient solar energy harvesting at elevated temperatures over time. Commercially, TinO x [3] and Pyromark [4] have been used as solar absorbers for low-to high-temperature applications. Spectrally-selective TinOx coatings could absorb 95% of incident solar radiation and emit only 4% thermal radiation, but its performance is optimal only around 100°C.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far more complex structures and materials show better solar selective properties than intrinsic ones so the main use of these materials is as a component of more complex coatings. The main exception is a proprietary coating known as Pyromark 2500 [76,77] which is used in high temperature receivers and which is reported to survive thousands of heating and cooling cycles to temperatures over 1000 1C and at 600 1C. It has an absorptivity of 0.96 and an emissivity of 0.8 at 800 1C [77] so is not particularly solar selective.…”
Section: Intrinsicmentioning
confidence: 99%